Hysteresis in Center of Mass Velocity Control during the Stance Phase of Treadmill Walking - Lee, Kyoung-Hyun; Chong, Raymond K. (Frontiers in Human Neuroscience, 2017)
Achieving a soft landing during walking can be quantified by analyzing changes in the vertical velocity of the body center of mass (CoM) just prior to the landing of the swing limb. Previous research suggest that walking speed and step length may predictably influence the extent of this CoM control. Here we ask how stable this control is. We altered treadmill walking speed by systematically increasing or decreasing it at fixed intervals. We then reversed direction. We hypothesized that the control of the center of mass (CoM) vertical velocity during the late stance of the walking gait may serve as an order parameter which has an attribute of hysteresis. The presence of hysteresis implies that the CoM control is not based on simply knowing the current input conditions to predict the output response. Instead, there is also the influence of previous speed conditions on the ongoing responses. We found that the magnitudes of CoM control were different depending on whether the treadmill speed (as the control parameter) was ramped up or down. Changes in step length also influenced CoM control. A stronger effect was observed when the treadmill speed was speeded up compared to down. However, the effect of speed direction remained significant after controlling for step length. The hysteresis effect of CoM control as a function of speed history demonstrated in the current study suggests that the regulation of CoM vertical velocity during late stance is influenced by previous external conditions and constraints which combine to influence the desired behavioral outcome.